MANAJEMEN LANSKAP UNTUK PENANGGULANGAN KONFLIK ANTARA MANUSIA DAN KOMODO (VARANUS KOMODOENSIS) DI DESA KOMODO TAMAN NASIONAL KOMODO - Tagang, Bonefasius Sarmando; Alfian, Rizki; Nailufar, Balqis (Fakultas Pertanian, 2016)
Human-wildlife conflict is one of the biggest challenges in conservation efforts. Conflict of Komodo dragons has been reported, but there is no comprehensive scientific data regarding the conflict. The study was conducted in Komodo Village, Komodo National Park, to see the distribution of Komodo dragon-human conflict in various habitat types (forests, villages, and savanna). The results of the study showed the incidence of eviction of Komodo dragons based on the experience of respondents. The Komodo dragon human conflict occurs in four habitat types with the largest number of conflicts occurring in village habitat types and savanna. Conflict is distributed along the border of village habitat types and savanna. Based on the results of the study, recommended prevention and conflict prevention measures to reduce the conflict of Komodo dragons in the future.Conflict distribution as many as 18 points of conflict were scattered within the Komodo National Park area in the Komodo village, which was spread in two places, Komodo Village and oh, the image was printed on the conflict point map. With many considerations and results of interviews with the people in the Komodo village, what needs to be done to overcome conflicts between humans and Komodo dragons in the Komodo village, with the creation of a barrier in the form of a buffer. Konflik manusia-satwa liar merupakan salah satu tantangan terbesar dalam upaya konservasi.Konflik manusia-biawak komodo telah dilaporkan, tetapi belum terdapat data ilmiah yang komprehensif mengenai konflik yang terjadi.Penelitian dilakukan di Desa Komodo, Taman Nasional Komodo, untuk melihat distribusi konflik manusia-biawak komodo di berbagai tipe habitat (hutan, desa, dan savana).Hasil penelitian menunjukkan kejadian pengusiran terhadap biawak komodo berdasarkan pengalaman responden.Konflik manusia biawak komodo terjadi di empat tipe habitat dengan jumlah konflik terbesar terjadi di tipe habitat desa dan savana.Konflik terdistribusi di sepanjang perbatasan tipe habitat desa dan savana.Berdasarkan hasil penelitian, direkomendasikan tindakan pencegahan dan penanggulangan konflik untuk mengurangi konflik manusia-biawak komodo kedepannya. Distribusi konfli ksebanyak 18 titik konflik yang tersebar di dalamkawasan Taman nasional komodo di desa komodo, yang tersebar di duatempatyaitudesa komodo dan oh Liang gambar tertera di peta titikkonflik.Dengan berbagai banyak pertimbangan dan hasil wawancara kepada masyarakat didesa komodo, yang perlu dilakukan untuk penanggulangan konflik antara manusia dan komodo didesa komodo, dengan pembuatan barrier yang berupa penyangga.